2001
DOI: 10.1093/ps/80.4.418
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heat Stress-Induced Alterations in Blood Acid-Base Status and Skeletal Muscle Membrane Integrity in Broiler Chickens at Two Ages: Implications for Meat Quality

Abstract: The effects of acute heat stress (AHS) on indices of respiratory thermoregulation and skeletal muscle damage (myopathy) were examined in broiler chickens at two ages (35 and 63 d of age); the relationships of these responses with changes in meat quality were assessed. Exposure to AHS significantly increased deep-body temperatures, panting-induced acid/base disturbances, and plasma creatine kinase (CK) activities, reflecting heat stress-induced myopathy (HSIM). The extent of the hyperthermia and disturbances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
156
3
19

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(190 citation statements)
references
References 23 publications
12
156
3
19
Order By: Relevance
“…Santiago et al (2005) compared commercial broilers slaughtered at 42 days and 53 days and also found higher water-holding properties in the MPS of the older birds but comparable pH and lightness values. Sandercock et al (2001) compared broilers with ages of 35 and 69 days and the authors foundcontrary to this study -no differences of the drip loss and colour score but a reduced pH 24 h p.m. in the older broiler.…”
Section: Discussionmentioning
confidence: 55%
“…Santiago et al (2005) compared commercial broilers slaughtered at 42 days and 53 days and also found higher water-holding properties in the MPS of the older birds but comparable pH and lightness values. Sandercock et al (2001) compared broilers with ages of 35 and 69 days and the authors foundcontrary to this study -no differences of the drip loss and colour score but a reduced pH 24 h p.m. in the older broiler.…”
Section: Discussionmentioning
confidence: 55%
“…This in agreement with the report of Mbajiorgu et al (2007) that increasing ascorbic acid supplementation increased dressing percentage and breast meat yield at 42 days old Ross 308 broilers. Hot conditions negatively affect yield and quality of broiler breast meat (Leenstra and Cahaner, 1992;Sandercock et al, 2001). This finding shows that with addition of vitamin C to drinking water of broilers, this effect of heat stress could be ameliorated.…”
Section: Discussionmentioning
confidence: 87%
“…These elevations indicate muscle cell membrane disruption and permeability, which led to subsequent skeletal muscle damage and fatigue (Sandercock et al, 2001). Scheffler and Gerrard (2007) indicated that damage on muscle membranes is an important factor that leads to a reduction in meat quality, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%